2015
DOI: 10.2485/jhtb.24.54
|View full text |Cite
|
Sign up to set email alerts
|

New Biodegradable Implant Material Containing Hydrogel with Growth Factors of Lyophilized PRF in Combination with an nHA/PLGA Scaffold

Abstract: The temperature-sensitive triblock copolymer poly-(D, L-lactic acid-co-glycolic acid) (PLGA)-polyethylene glycol (PEG)-PLGA (PLGA-PEG-PLGA) is an FDA-approved material that has the ability to provide a sustained release of drugs and/or proteins. Platelet-rich fibrin(PRF)is second generation platelet concentration that contains growth factors such as transforming growth factor-1 (TGF-1), platelet derived growth factor-AB (PDGF-AB), and insulin-like growth factor-I (IGF-I). These growth factors affect the migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…In contrast, it has been reported that lyophilized platelet products can release the vast majority of cytokines rapidly after 24‐h incubation (Zheng et al . ). In this study, cytokines were extracted using the lyophilized method and five representative cytokines, including TGF‐β1, PDGF‐BB, VEGF, IGF‐1 and bFGF, were detected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, it has been reported that lyophilized platelet products can release the vast majority of cytokines rapidly after 24‐h incubation (Zheng et al . ). In this study, cytokines were extracted using the lyophilized method and five representative cytokines, including TGF‐β1, PDGF‐BB, VEGF, IGF‐1 and bFGF, were detected.…”
Section: Discussionmentioning
confidence: 97%
“…Growth factors extracted from the CGF were prepared according to previously reported protocols with slight modifications (Zheng et al 2015). In brief, the fresh CGF clot was placed in a lyophilizer overnight.…”
Section: Quantification Of Representative Growth Factors In the Cgfmentioning
confidence: 99%
“…The CGF gel was collected from the middle layer of the samples (between the upper, platelet-poor plasma layer, and the lower, red blood cell layer) and pressed onto a membranous film as previously described [13]. CGF conditioned media were prepared as follows [24]: CGF membranes (each membrane was prepared from 2 mL blood) were placed in lyophilizer overnight. The lyophilized CGF membranes were ground into powder and immersed into 2 mL DMEM at 37 °C for 24 h. The media were collected and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…LPCs express their growth factors more slowly than PCs. This was discovered in a study by Zheng [13] when they attempted to combine nano-hydroxyapatite (nHA), L-lactic acid-co-glycolic acid (PLGA), and the hydrogel (nHA/PLGA/Gel) scaffold with LPCs. The in vitro release experiments showed that the composite scaffold allowed for gradual and continuous release of PRF-derived growth factors.…”
Section: Overview Of Lyophilization For Platelet Concentratesmentioning
confidence: 99%
“…However, PCs were designed for immediate and short-term use (for up to 14-days); thus, this approach somewhat limits their therapeutic value [11,12]. As longer periods are reportedly required for the enhancement of bone regeneration, more effective methods for the delivery of growth factors over longer time-periods have been sought [13]. Furthermore, PCs are processed from autologous blood prior to clinical use, and, therefore, their bioactivity can vary between individuals.…”
Section: Introductionmentioning
confidence: 99%